การรับรู้ข่าวสารทางการเมืองของชาวภูมิซรอลจากรัฐบาล: ศึกษากรณี วิกฤตการณ์เขาพระวิหาร ในช่วงพ.ศ. 2551-2552 - พิริยะพลิน, ธีรัตม์ (Journal of Graduate School of Commerce-Burapha Review, 2016)
การวิจัยเรื่อง การรับรู้ข่าวสารทางการเมืองของชาวภูมิซรอลจากรัฐบาล: ศึกษากรณีวิกฤตการณ์เขาพระวิหาร ในช่วง พ.ศ. 2551-2552” เป็นการวิจัยเชิงคุณภาพ (Qualitative research) โดยใช้การวิเคราะห์เนื้อหา (Content analysis) เป็นแนวทางในการวิจัย และใช้บริบท (Context) เป็นกรอบในการวิเคราะห์ซึ่งมีวัตถุประสงค์ 3 ประการ คือ 1) เพื่อศึกษา กระบวนการรับรู้ข่าวสารทางการเมืองของชาวภูมิซรอลจากรัฐบาล ในกรณีวิกฤตการณ์เขาพระวิหาร ในช่วง พ.ศ. 2551-2552 2) เพื่อศึกษาบริบททางการเมือง เศรษฐกิจ สังคม ที่ส่งผลต่อกระบวนการรับรู้ข่าวสารทางการเมืองของชาวภูมิซรอลจาก รัฐบาล ในกรณีวิกฤตการณ์เขาพระวิหาร ในช่วง พ.ศ. 2551-2552 3) เพื่อศึกษาผลกระทบที่ตามมาของกระบวนการรับรู้ ข้อมูลข่าวสารทางการเมืองของชาวภูมิซรอลจากรัฐบาล ในกรณีวิกฤตการณ์เขาพระวิหาร ในช่วง พ.ศ. 2551-2552 ผลจากการศึกษาพบว่า 1) กระบวนการรับรู้ข่าวสารการเมืองจากรัฐบาลของชาวภูมิซรอลมีการรับรู้ข้อมูลข่าวสารน้อย และมักขึ้นอยู่กับความสนใจของแต่ละบุคคล สาเหตุที่ต้องการรับรู้ข่าวสารเพราะอยากทราบข้อเท็จจริงที่เกิดขึ้น ในพื้นที่ เพื่อปรับตัวและเตรียมรับสถานการณ์ เนื้อหาของข่าวสารที่ติดตามจะเกี่ยวกับปัญหาข้อพิพาทเรื่องเขตแดน ไทย-กัมพูชา โดยรับรู้ข้อมูลข่าวสารจากโทรทัศน์ วิทยุ หนังสือพิมพ์ อินเตอร์เน็ต และจากการพูดคุยสนทนา แลกเปลี่ยน ข้อมูลข่าวสารในหมู่คนใกล้ชิด เพราะหน่วยงานของรัฐบาลในพื้นที่ให้ข้อมูลข่าวสารแก่ประชาชนน้อยมาก ข้อมูลข่าวสาร ที่เผยแพร่ออกไปไม่ตรงกับข้อเท็จจริงที่เกิดขึ้นในพื้นที่ และมักจะอ้างความมั่นคงเป็นหลักทำให้ประชาชนเกิดความสับสน นอกจากนั้นการปฏิบัติงานของเจ้าหน้าที่ขาดความต่อเนื่อง ผู้บริหารระดับสูงของรัฐบาลต้องลงไปดูพื้นที่เกิดเหตุจริง ด้วยตนเอง 2) บริบททางการเมือง เศรษฐกิจ และสังคมที่ส่งผลต่อกระบวนการรับรู้ข่าวสารทางการเมืองของประชาชน ชาวภูมิซรอลจากรัฐบาลพบว่ามีน้อยมาก เพราะเนื้อหาของข่าวสารที่เผยแพร่ออกไปขาดความชัดเจน มีลักษณะบิดเบือน คลุมเครือช่องทางในการให้ข่าวสารเป็นไปด้วยความล่าช้าไม่ทันเหตุการณ์และข่าวที่นำเสนอออกไปนั้นขาดการกลั่นกรอง ข้อมูลที่นำเสนอไม่สอดคล้องกับความต้องการที่ประชาชนอยากจะรับรู้ ช่องทางในการสื่อสารของรัฐบาลยังมีไม่เพียงพอ ทำให้ประชาชนขาดโอกาสในการรับรู้บริบททางการเมือง เศรษฐกิจ และสังคมอย่างรอบด้าน ส่วนมากใช้กลไกของรัฐบาล ในพื้นที่ให้ข้อมูลข่าวสารที่เกี่ยวกับการอพยพหลบภัย ปัญหาด้านการครองชีพประชาชนต้องช่วยเหลือตัวเองตาม ความถนัดของแต่ละคน 3) ผลกระทบที่ชาวภูมิซรอลได้รับมากที่สุดคือด้านจิตใจเกิดความวิตกกังวลกับความปลอดภัย ในชีวิตและทรัพย์สิน ความคิดแตกแยกมีปัญหาการทะเลาะเบาะแว้งตามมา ประชาชนต้องปรับตัวในการอยู่อาศัย การทำมาหากิน การใช้ชีวิตประจำวัน โดยต้องตั้งสติเพื่อเตรียมพร้อมรับสถานการณ์ที่อาจเกิดขึ้นตลอดเวลา การปฏิบัติงาน ของเจ้าหน้าที่มักออกคำสั่งให้ประชาชนทำตาม ทิ้งปัญหาต่างๆ ไว้ให้แก้ไขกันเอง การปิดเขาพระวิหารมีผลกระทบมาก จนทำให้เกิดการว่างงานและนำไปสู่ปัญหาอื่นๆ ประชาชนในพื้นที่ขาดความรัก ความสามัคคีและความเอื้ออาทรต่อกัน มากขึ้น เพราะทุกคนต่างเอาตัวรอด ผลกระทบจากวิกฤตการณ์เขาพระวิหารนั้นส่วนหนึ่งเป็นเพราะรัฐบาลขาดความต่อ เนื่อง แต่ละรัฐบาลได้ใช้วิธีการแก้ปัญหาตามกระแส รัฐบาลไม่ได้สนใจที่จะแก้ปัญหาอย่างจริงจังและขาดข้อมูลเชิงลึก ในพื้นที่ทำให้ประชาชนไม่สนใจการแก้ไขปัญหาของรัฐบาล เพราะมีความล่าช้าไม่ทันเหตุการณ์ที่เกิดขึ้น PERCEPTION OF GOVERNMENT INFORMATION OF THE PHUMSRAL: A CASE STUDY OF CRISIS OF KHAO PRA VIHAN, 2008 – 2009 Theerath Piriyaparin Graduate School of Commerce, Burapha University, Chon Buri 20131, Thailand This study of perception of government information of the Phumsral via a case study of crisis of Khao Phra Viharn during 2008-2009 is designed to be a qualitative research based on content analysis as a research approach while context is used as a framework for analyzing the content. Its objectives cover 3 main aspects as follows 1) To investigate the process of perception of government information of the Phumsral via a case study of crisis of Khao Phra Viharn during 2008-2009 2) To explore political, economic and social context influencing perception of government information of the Phumsral via a case study of crisis of Khao Phra Viharn during 2008-2009 3) To discuss the subsequent impact from perception of government information of the Phumsral via a case study of crisis of Khao Phra Viharn during 2008-2009. Findings from the study indicate that 1) They show strong sense of preservation of mother earth of Thailand and would like to know about the situation in the area in order to adapt and prepare themselves against the situation. The content of news and information related to dispute concerning Thai – Cambodian border distributed to them via television and radio broadcasting, newspaper, internet and discussion with others in the community while local government agencies provide for the public relatively inadequate information part of which does not reflect the fact existing in the area. Such information is provided based on the national security reason thus leading to public confusion sometime. In addition, the operation of government officer has not been continually performed and therefore requiring top-level executives to visit the area by themselves. 2) The political, economic and social context reveals minimal effect upon the perception of government information of the Phumsral as the content of such information is lack of clearness, distorted and ambiguous. Official distribution channels do not provide updating information to meet the requirement of the public and are sometime inadequate resulting in loss of opportunity for the public to understand comprehensive political, economic and social context. Government agencies in the area are used for providing information concerning evacuation and migration while people in the community have to help themselves based on their individual skills resulting in that the local communities have been most affected mentally. 3) They have been under stress and anxiety about their safety in life and properties. There are disagreements and disputes. People have to adapt their living, earning and routine life and also have to always be well-prepared to respond to the incident properly. The officers have always given directions to people which later require to be clarified and resolves among themselves. Closing the border at Khao Phra Viharn has lead to material consequences such as unemployment and other problems. The community’s love and unity has been deteriorated as each member has to survive oneself against to impact of this crisis. Problems have been partly worsened by the discontinued action by the Government as most problems are corrected temporarily due to lack of in-depth knowledge and understanding of the actual fact in the area. As a result, people in the area disregard most of the measures initiated by the Government as they are not implemented in a timely manner.